Advances in audio and speech signal processing technologies and applications - Perez-Meana, Hector, 1954- (Hershey, PA : Idea Group Pub., 2007)
"This book provides a comprehensive approach of signal processing tools regarding the enhancement, recognition, and protection of speech and audio signals. It offers researchers and practitioners the information they need to develop and implement efficient signal processing algorithms in the enhancement field"--Provided by publisher.
Ηλεκτρονικό βιβλίο
Keywords: Sound -- Recording and reproducing; Signal processing -- Digital techniques; Speech processing systems; Electronic books